Cyclotron production of manganese-52: a promising avenue for multimodal PET/MRI imaging - Francesca Porto; Sara Cisternino; Emiliano Cazzola; Giorgia Speltri; Liliana Mou; Alessandra Boschi; Lorenza Marvelli; Giovanni Di Domenico; Antonella Pagnoni; Lucia De Dominicis; Irene Calliari; Claudio Gennari; et al. (SpringerOpen, 2024)
Abstract Background The integration of positron emission tomography (PET) and magnetic resonance imaging (MRI) holds promise for advancing diagnostic imaging capabilities. The METRICS project aims to develop cyclotron-driven production of 52Mn for PET/MRI imaging. Results Using the 52Cr(p,n)52Mn reaction, we designed chromium metal targets via Spark Plasma Sintering and developed a separation procedure for isolating 52Mn. Labeling tests were conducted with traditional chelators (i.e. S-2-(4-Isothiocyanatobenzyl)-1,4,7,10-tetraazacyclododecane tetraacetic acid) and the 1.4-dioxa-8-azaspiro[4.5]decane-8- carbodithioate ligand to produce radioactive complexes suitable for PET/MRI applications. Our methodology yielded high-quality 52Mn suitable for PET radiopharmaceuticals and PET/MRI imaging. Preliminary studies on phantom imaging using microPET and clinical MRI demonstrated the efficacy of our approach. Conclusions The developed technology offers a promising avenue for producing 52Mn and enhancing PET/MRI imaging capabilities. Further in vivo investigations are warranted to evaluate the potential advantages of this hybrid imaging technique.